Semantyczna skala języków a „hierarchia” sposobów myślenia. Rozważania w świetle myśli Stanisława Lema - Gomułka, Łukasz (Hybris, 2016)
In his texts, Stanisław Lem on one hand takes into consideration ambiguity, polyinterpretation and muddying of contextual and connotative nature of a natural language. On the other hand, he takes into account evolutionary character of that state of affairs, that is to say the natural language (in its abundance of variants) is the one and particular so that a man is capable of notionally grasping the continuously changing world of nature and culture. This last aspect is especially crucial because, firstly, a language forms the basis of culture. Secondly, it allows to understand and express humans’ knowledge about the world — and this knowledge is continuously developing and complicating itself. In this text I elaborate on the above mentioned Lem’s position on the natural language, I also introduce interconnected notions of ‘semantic scale of languages’ and ‘hierarchy of lines of thought’. The last one comprises three stages: (1) pre-set thinking (pre-logical), (2) logical thinking, (3) creative thinking (intuitive). Each of the mentioned lines of thought is characterized by a corresponding language with definite features.